Implementation of Augmented Reality for Earth Layer Structure on Android Based as a Learning Media - Deli Deli (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2020)
Implementation of Augmented Reality for Earth Layer Structure on Android Based as A Learning Media isa research that aims to help in presenting material to Elementary School children. The research methodchosen in the completion of this study uses the 4D method (Define, Design, Develop and Disseminate) witha data collecting method using Technology Acceptance Model (TAM) built one construct with threedimensions of user assessment level of technology acceptance to support the basis of questionnaire design.AR design supported by 3D models, in order to be able to support the details of each explanation of thematerial contained, thus helping users to understand the material and ease of interaction on the media.The final result obtained in this research is that the application is stated to be able to help the school, it is used as a media display in the classroom so students do not need to imagine themselves, but simply byusing learning media is able to present the material to students.Keywords: Learning Media, 4D Method, User Acceptance Test, Augmented reality, Android.